Composition, sources, and bioavailability of nitrogen in a longitudinal gradient from freshwater to estuarine waters. (15th June 2018) - Jani, Jariani; Toor, Gurpal S.
Abstract: Nitrogen (N) transport from land to water is a dominant contributor of N in estuarine waters leading to eutrophication, harmful algal blooms, and hypoxia. Our objectives were to (1) investigate the composition of inorganic and organic N forms, (2) distinguish the sources and biogeochemical mechanisms of nitrate–N (NO3 –N) transport using stable isotopes of NO3 − and Bayesian mixing model, and (3) determine the dissolved organic N (DON) bioavailability using bioassays in a longitudinal gradient from freshwater to estuarine ecosystem located in the Tampa Bay, Florida, United States. We found that DON was the most dominant N form (mean: 64%, range: 46–83%) followed by particulate organic N (PON, mean: 22%, range: 14–37%), whereas inorganic N forms (NOx –N: 7%, NH4 –N: 7%) were 14% of total N in freshwater and estuarine waters. Stable isotope data of NO3 − revealed that nitrification was the main contributor (36.4%), followed by soil and organic N sources (25.5%), NO3 − fertilizers (22.4%), and NH4 + fertilizers (15.7%). Bioassays showed that 14 to 65% of DON concentrations decreased after 5-days of incubation indicating utilization of DON by microbes in freshwater and estuarine waters. These results suggest that despite low proportion of inorganic N forms, the higher concentrations and bioavailability of DON can be a potential source of N for algae and bacteria leading to water quality degradation in the estuarine waters. Graphical abstract: Highlights: Dissolved organic nitrogen (DON) was the dominant N form in freshwater and estuarine sites. Stable isotopes data revealed that NO3 –N originated from mixing of multiple sources. Nitrification was the most dominant source of NO3 –N in freshwater and estuarine sites. DON was more bioavailable in the estuarine (50–65%) than freshwater (14–36%) sites.